Anchoring Universities - Badat, S. M. (South African Journal of Higher Education, 2023)
Book Review: Samuel Fongwa, Thierry Luescher, Ntimi Mtawa and Jesmael Mataga (eds.) 2015 Universities, Society and Development: African Perspectives of University Community Engagement in Secondary Cities: Stellenbosch: Sun Press.